A rehabilitation of a metaphysical problematics in neopragmatism - Synycja, Andrij (Actual Problems of Mind, 2017)
The paper discloses the process of a rehabilitation of a metaphysical problematics within such a direction of analytic philosophy as neopragmatism. The author claims that this process initiated by W.V.O. Quine is still in progress, since the metaphysical problematics should be preceded by a thorough logicolinguistic analysis of a scientific theory.